GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD INPRES TAMARUNANG KABUPATEN BANTAENG - Nur, Ahmad Fadhlan; Madani, Muhlis; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to determine the leadership style of school principals in improving teacher performance at SD Inpres Tamarunang. The method used in this research is qualitative with a descriptive approach and data is collected using observation, interview and documentation techniques using the Hersey and Blanchard style policy implementation model. With good leadership in schools, teacher performance can improve The results of the research show that the application of the leadership style of the principal of SD Inpres Tamarunang, Bantaeng Regency by directing/directing, coaching/coaching, supporting/supporting and delegating/delegating has been implemented well in improving teacher performance at SD Inpres Tamaraunang, Bantaeng Regency.